Pengembangan Media Pembelajaran Bahasa Indonesia Berbasis Storyjumper - Nur Rizka Laila (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the development of Indonesian language learning media based on StoryJumper in the form of a digital book entitled Belajar Bahasa Indonesia Itu Seru! for Grade I elementary school students. This research employs a descriptive qualitative approach focusing on the characterization, structure, and content of the developed digital learning media. The data were collected through documentation of the StoryJumper digital book, including text content, illustrations, learning activities, and supporting features, and were analyzed using content analysis. The results show that the developed media presents Indonesian language learning materials through contextual illustrated stories equipped with vocabulary enrichment and structured learning activities. The media integrates four language skills, namely listening, speaking, reading, and writing, which are presented systematically in each chapter. In addition, the use of Canva as a supporting design tool and the integration of audio elements further enhance the attractiveness and learning experience of students. Overall, the StoryJumper-based digital book has strong potential to be used as innovative digital learning media that is engaging, communicative, and aligned with the characteristics of elementary school students. Keywords: StoryJumper; Digital Learning Media; Indonesian Language Learning; Language Skills